The effects of dependence and function on costs of care for Alzheimer's disease and mild cognitive impairment in Ireland†. (30th May 2012) - Gillespie, P; O'Shea, E; Cullinan, J; Lacey, L; Gallagher, D; Ni Mhaolain, A; ,
<x xml:space="preserve">Abstract</x> Objective To explore the incremental effects of patient dependence and function on costs of care for patients with Alzheimer's disease (AD) and amnestic mild cognitive impairment (MCI) in Ireland. Methods Cost analysis based on reported resource use for a cross‐section of 100 community‐based people with AD and MCI. Formal care included general practice visits, hospitalizations, outpatient clinic consultations, accident and emergency visits, respite care, meals on wheels services and other health and social care professional consultations. Informal care included time input provided by caregivers. Resource unit costs were applied to value formal care and the opportunity cost method was used to value informal care. Patient dependence on others was measured using the Dependence Scale and patient functional capacity using the Disability Assessment for Dementia scale. Multivariate regression analysis was used to model the cost of care. Results Both dependence and function were independently and significantly associated with total formal and informal care cost: a one point increase in dependence was associated with a €796 increase in total cost and a one point improvement in function with a €417 reduction in total cost over 6 months. Patient function was significantly associated with formal care costs, whereas patient function and dependence were both significantly associated with informal care costs. Conclusion The costs of care for patients with AD and MCI in Ireland are substantial. Interventions that reduce patient dependence on others and functional decline may be associated with important economic benefits. Copyright © 2012 John Wiley & Sons, Ltd.